Novice Therapists' Perception and Use of Self-Care - Hammerton, Rachel (Université d'Ottawa / University of Ottawa, 2019)
Self-care is necessary for psychotherapists to prevent burnout and to provide ethical services for clients. Counselling students often recognize the need for self-care, but neglect to implement it, preventing them from building the necessary practices to endure hardships related to practicing psychotherapy. Previous research, such as Butler and colleague’s work (2017), has examined the importance of self-care in counselling education, but has not examined how it is applied in practice. Therefore, this project’s research questions included: 1) How do novice therapists engage in professional self-care? 2) How do novice therapists bridge the gap between conceptual knowledge and practice of professional self-care? 3) What are the barriers to self-care? Thematic Analysis (TA) was used to distil meaning from common experiences of participants. Four psychotherapists with an average of 1.5 years of experience were interviewed using an in-depth semi-structured interview protocol. Eighteen subthemes were generated from the data, further categorized under four themes: (1) obstacles to self-care; (2) work-life balance; (3) pathways to self-care; and (4) effects of self-care. Implications of this research include structured self-reflection in counsellor training programs, integration of flexibility and self-care provisions in workplace cultures, and a strong policy emphasis on the need for counsellor self-care and improving professional guidelines to allow for counsellor self-care practices.
Keywords: Therapist Self-Care; Counsellor Education; Ethical Therapeutic Practices; Psychotherapy